IDENTITY OF CULTURE OF BLACKS AND WHITES IN TONI MORRISON’S SONG OF SOLOMON (A PERSPECTIVE OF POSTMODERNISM) - Supriyatno Supriyatno; Luky Indarwati; Maria Ariastuti (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2023)
The cultural identity in a society is the characteristic and signifier to the existence and dimension of society in their life. Life of community in the broadest sense exists in paradigm of reflection and representation in the plots of norm, ideology, tradition and aesthetic involved in and it should not be the dichotomy in space and time in transferring the meaning of life. It is the forms of integrity, responsibility in orders of values, hope, ideals and future. The article represents the life of human being in following, encouraging, accompanying, even fighting for how to reach the cultural identity in terms of rational and historical times. Colored with the problems of social stratification, race, and gender, this novel tries to convey the forms of paradoxical analyses and sharply elaborated in the structure of oxymoron in which imply on the studies of culture in a society to find out the self-identity. The analyses of the research are in the approach of post-modernism discussed as the reaction to the established modern era and its colors, meanwhile the data analyzed in terms of qualitative method with the techniques of interpretative qualitative in the steps of data comprehensively read, interpretation of meaning and critical analysis.